Compact Circularly Polarized E-Shaped Crossed-Dipole Antenna - Kedze, Kam Eucharist; Kim, Youngwook; Park, Ikmo (14th European Conference on Antennas and Propagation, EuCAP 2020, 2020)
This study proposes a circularly polarized (CP) compact E-shaped crossed-dipole antenna comprising two printed crossed-dipole arms and a pair of vacant quarter printed rings. The design goals are attained through the rotation and folding of the arms of the conventional crosseddipole antenna to achieve a miniaturized CP antenna. A compact antenna is designed by rotating half of the crossed dipole by 90° and folding its arms to form a small E-shaped antenna that generates CP radiation with satisfactory performance. The performance of the proposed antenna is discussed and confirmed both numerically and experimentally. This antenna has overall dimensions of 26.8 mm × 30.6 mm × 0.508 mm (0.28k × 0.32k × 0.0055k at 3.22 GHz), a measured |S11|<-10dB impedance bandwidth of 2.75-3.6 GHz (26.77%), and a simulated 3-dB axial ratio bandwidth of 3.0-3.45 GHz (13.95%).
Keywords: Axial ratio bandwidth; Circularly polarized; Compact antenna; Crossed dipoles; Crossed-dipole antenna; Design goal; E-shaped; Impedance bandwidths; antenna miniaturization; broadband; circular polarization; crossed dipole; E-shaped antenna.